The Malakok Tradition as a Customary Kinship Mechanism for Building Interreligious Tolerance in Minangkabau Society - Selvi Rahmadania; Novi Hendri (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2026)
The Malakok tradition, locally known as Mangaku Induak, is a customary kinship mechanism through which individuals are incorporated into the social and genealogical structure of Minangkabau society. Beyond its function of establishing customary belonging, Malakok may also provide a social space for negotiating difference and fostering interreligious relations. This study aims to examine the process through which Malakok is practiced and to analyze its role in generating social acceptance, kinship solidarity, and interreligious tolerance in Pauh Duo District, South Solok Regency, West Sumatra. Employing a qualitative field research design, data were collected through observation, in-depth interviews, and documentation involving interreligious Malakok participants, niniak mamak, customary leaders, religious leaders, community leaders, and local residents. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that Malakok involves family deliberation, approval by niniak mamak, and a customary ceremony that formally legitimizes an individual's incorporation into a Minangkabau kinship network. More importantly, the practice extends customary belonging across religious boundaries: Christian and Catholic individuals can be incorporated into customary families without relinquishing their religious identities. Interreligious tolerance is subsequently sustained through familial relations, participation in communal activities, mutual assistance, and everyday solidarity. The study demonstrates that Malakok functions not merely as a mechanism of customary integration but also as a locally embedded institution for negotiating religious difference, strengthening social cohesion, and sustaining interreligious coexistence in a plural society.